2017
DOI: 10.1007/s00705-017-3573-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Efficacy and safety of sofosbuvir plus ribavirin for treatment of cirrhotic patients with genotype 4 hepatitis C virus in real-life clinical practice

Abstract: Egypt has the highest hepatitis C virus (HCV) prevalence in the world. Sofosbuvir is a new highly effective drug for treatment of HCV infection. Compared to previous treatments, sofosbuvir-based regimens provide a higher cure rate, fewer side effects, and a two- to fourfold reduced duration of therapy. The aim of this study was to evaluate the antiviral efficacy, safety, and tolerability of sofosbuvir plus ribavirin in Egyptian patients with liver cirrhosis due to chronic HCV infection. We studied 2400 cirrhot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 22 publications
4
26
2
Order By: Relevance
“…In fact, we identified several studies that specifically focus on elderly populations while others reported age‐specific subgroup analyses. While most of the studies reported comparable efficacy of DAAs in the elderly compared to younger patients, some raised concerns that higher rates of treatment failure may specifically affect subgroups with other negative predictive factors, including cirrhosis and HCV genotypes 3 and 4 . Moreover, some studies also reported higher rates of SAEs and treatment discontinuation in the elderly .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we identified several studies that specifically focus on elderly populations while others reported age‐specific subgroup analyses. While most of the studies reported comparable efficacy of DAAs in the elderly compared to younger patients, some raised concerns that higher rates of treatment failure may specifically affect subgroups with other negative predictive factors, including cirrhosis and HCV genotypes 3 and 4 . Moreover, some studies also reported higher rates of SAEs and treatment discontinuation in the elderly .…”
Section: Discussionmentioning
confidence: 99%
“…While most of the studies reported comparable efficacy of DAAs in the elderly compared to younger patients, some raised concerns that higher rates of treatment failure may specifically affect subgroups with other negative predictive factors, including cirrhosis 24 and HCV genotypes 3 and 4. [25][26][27] Moreover, some studies also reported higher rates of SAEs and treatment discontinuation in the elderly. 18,[28][29][30] These findings have raised concerns whether a 'treat all' strategy is justified given the lack of a comprehensive risk-benefit analysis in this particular patient population.…”
Section: F I G U R E 2 Subgroup Analysis For Non-sustained Virologic mentioning
confidence: 99%
“…proximately 13% of all HCV infections worldwide, 1 with the highest prevalence occurring in Egypt (93% of genotype 4 worldwide and 15% of Egyptians), 2,3 where it is a leading cause of liver cirrhosis, hepatic cell carcinoma (HCC) and mortality. 4 Liver transplant (LT) has become a frequently used treatment strategy for end-stage liver disease (ESLD), HCC and acute liver failure, as it provides the only possibility of cure, long-term survival and improved quality of life.…”
Section: Chronichepatitis C Virus (Hcv) Infection Genotype 4 Occurs Imentioning
confidence: 99%
“…The participants in groups II and III were between 18 and 75 years of age and had detectable HCV RNA by PCR. The patients were excluded from these groups if they were younger than 18 years or older than 75 years of age, or had one of the following criteria: total bilirubin (T.Bil) >3 mg/dL, serum albumin <2.8 mg/dL, international normalized ratio ≥1.7, platelet count <5000/mm 3…”
Section: Group (I)mentioning
confidence: 99%
“…HCV genotype 4 ( G4 ) is the common genotype in the Middle East, Northern Africa and Sub‐Saharan Africa. In Egypt, 93% of HCV patients are infected with G4 …”
Section: What Is Known and Objectivementioning
confidence: 99%